Eficiência agroeconômica em sistemas de produção de hortaliças e grãos em ambiente semiárido - Nunes, Renato Leandro Costa (2019)
Today, increasing food demand and water scarcity stimulate the creation of appropriate agricultural production methods as well as irrigation management to supply them. Among these methods is the crop intercropping system and irrigation water management used by the MOPECO model of cultivation. Thus, the objective of this work was to evaluate the agroeconomic efficiency in intercropping systems of vegetables and grains in the semi-arid environment, as well as to determine the limited quantity optimized in agricultural properties using the ORDI methodology for limited volumes of water. For the intercropping system, the experimental design was a randomized block design with four replications, with the treatments arranged in a 4 x 3 factorial scheme, where the first factor consisted of four amounts of Calotropis procera incorporated in the soil (20; 35; 50 and 65 t ha-1 on a dry basis) and the second one of three spatial arrangements (2:2; 3:3 and 4:4) in two crop seasons. Regarding the optimization of the amount of water in agricultural properties was verified in the MOPECO model of crop with analyzes for two hypothetical irrigated properties. The first simulation was performed with experimental data of garlic and barley for years 2015, 2016 and 2017 in Aguas Nuevas (Albacete). For the second simulation, the data used were collected from an agricultural property involving barley, corn and onion crops for the years 2014 and 2015 in Minaya (Albacete). In both simulations the ORDI methodology and the traditional irrigation of the crops (T) were compared for a hypothetical 100 hectare agricultural property with different total volumes of irrigation water availability. Climatic data of the station of the "Servicio Integral de Asesoramiento al Regante" and economic information published by the "Anuario de Estadística Agroalimentaria" were used in the MOPECO model. The main results obtained in intercropping were: 1) Greater responsivity agro-economic responsiveness of the intercropping of radish and cowpea-vegetable was obtained with the incorporation of 56.06 t ha-1 of C. procera; 2) It was obtained in the spatial arrangements 3:3 and 4:4 had better agronomic and economic responsiveness; 3) The radish was the dominant culture and the cowpea-vegetable dominated; 4) Highest agronomic and economic efficiencies of the radish intercropped with cowpeavegetable was achieved in the amounts of 59.97 and 45.91 t ha-1 of C. procera biomass incorporated in the soil; 5) There was no influence of the spatial arrangements on the economic efficiency of associations of radish with cowpea-vegetable; 6) In the MOPECO model of cultivation, the ORDI methodology was more profitable agroeconomically than the traditional one if the agricultural property had low volumes of water for irrigation and 7) This methodology was more appropriate when used with low yield crops, such as barley and corn, and it is not suitable for garlic and onion crops